Legal Developments On The Use Of Protected Forest Areas For Geothermal Power - Nugrahani, Dian (Fakultas Hukum Universitas Islam Malang, 2024)
The latest developments related to indirect Geothermal utilization in conservation areas in connection with the issuance of Law Number 11 of 2020 concerning Job Creation, which includes the forestry sector and its amendments through Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation. The creation of the facilities provided by the Government can positively impact the ease of Geothermal utilization. The research method used is a normative juridical method. The method of data analysis in this study was carried out qualitatively by elaborating and analyzing various secondary data and legal materials obtained in order to answer each of the problem formulations. Conservation forest areas in the Sumatra region have many animals that must be preserved. Geothermal utilization is required to follow specific standards and norms by not damaging the landscape area of forest areas.